2012
DOI: 10.1080/17470218.2012.657656
|View full text |Cite
|
Sign up to set email alerts
|

On the time course of exogenous cueing effects in bilinguals: Higher proficiency in a second language is associated with more rapid endogenous disengagement

Abstract: Previous investigations have demonstrated a bilingual advantage on various aspects of executive control. It remains unclear how the language proficiency of bilinguals might relate to the mechanisms involved in attentional disengagement. In the present investigation, we tested the hypothesis that high bilingual proficiency would lead to a more rapid endogenous disengagement of attention from task-irrelevant peripheral cues. We predicted that more rapid attentional disengagement would result in an earlier appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
2
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 29 publications
6
64
2
1
Order By: Relevance
“…Rapid disengagement is one of the mechanisms believed to be responsible for reduced switch costs (Allport & Wylie, 2000), although the finding of reduced switch costs for bilinguals is not always replicated (Hernández, Martin, Barceló, & Costa, 2013). Using an inhibition of return paradigm, Mishra and colleagues (2012) showed that high proficiency bilinguals showed the inhibition of return effect at earlier stimulus-onset-asynchronies than low proficiency bilinguals, a pattern consistent with more rapid disengagement from the preceding irrelevant distractor (Klein, 2000). Thus, higher proficiency in a second language is associated with more rapid disengagement.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Rapid disengagement is one of the mechanisms believed to be responsible for reduced switch costs (Allport & Wylie, 2000), although the finding of reduced switch costs for bilinguals is not always replicated (Hernández, Martin, Barceló, & Costa, 2013). Using an inhibition of return paradigm, Mishra and colleagues (2012) showed that high proficiency bilinguals showed the inhibition of return effect at earlier stimulus-onset-asynchronies than low proficiency bilinguals, a pattern consistent with more rapid disengagement from the preceding irrelevant distractor (Klein, 2000). Thus, higher proficiency in a second language is associated with more rapid disengagement.…”
Section: Introductionmentioning
confidence: 92%
“…There is some existing evidence that bilinguals disengage from previous distracting information more rapidly than monolinguals (Grundy & Keyvani Chahi, 2017; Mishra, Hilchey, Singh, & Klein, 2012). Task-switching studies that examine the cost of switching from one task to another versus repeating the same task have shown that bilinguals show smaller switch costs than monolinguals (Prior & Gollan, 2011; Prior & MacWhinney, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In monolinguals, a delayed response on the 500ms probe indicated residual inhibition of the previous competitor. Critically, in bilinguals (but not monolinguals), better nonlinguistic Stroop performance was associated with shorter response times to the competitor priming probe, suggesting faster resolution of linguistic competition (Blumenfeld & Marian, 2011; for similar findings in the nonlinguistic domain, see Mishra, Hilchey, Singh, & Klein, 2012). Similar patterns have recently been identified linking quicker cross-linguistic competition resolution to better nonlinguistic Stroop performance in bilinguals (e.g., Blumenfeld & Marian, 2013; Mercier et al, 2014).…”
Section: Introductionmentioning
confidence: 92%
“…Such heterogeneity in linguistic experiences has been shown to have led to diverse cognitive consequences, such as level of language proficiency (e.g. Mishra, Hilchey, Singh, & Klein, 2012), stage of second language acquisition (early bilingual vs. late bilingual, Kalia, Wilbourn, & Ghio, 2014), the degree of bilingualism (dominant vs. balanced bilingual, Goral, Campanelli, & Spiro, 2015), pattern of language use, varying experience with frequent language switch (Soveri, Rodriguez-Fornells, & Laine, 2011), the similarity between a bilingual speakers' two languages (Coderre & van Heuven, 2014, but see Paap et al, 2015a) and multilingualism (Poarch & van Hell, 2012). In addition, there are factors that are closely related to bilingualism or factors that drive the different language experiences, which at the same time are related to general cognitive performances.…”
Section: Factors That Potentially Drive the Inconsistencymentioning
confidence: 99%